Vaccination against Murine Toxoplasmosis Using Recombinant Toxoplasma gondii SAG3 Antigen Alone or in Combination with Quil A - Lee, Young-Ha (Yonsei University College of Medicine, 2007)
PURPOSE: Surface antigen 3 (SAG3) of Toxoplasma gondii is very similar in structure to the major surface antigen 1 (SAG1). Although numerous studies have supported the importance of SAG1 in protection against T. gondii infection, few reports exist on SAG3. MATERIALS AND METHODS: Glutathione-S-transferase (GST)-fused SAG3 of T. gondii (rSAG3) were immunized into BALB/c mice alone or in combination with Quil A (rSAG3/Quil A), and then evaluated the protective immunity in vivo and in vitro against murine toxoplasmosis. RESULTS: Immunization with rSAG3 or rSAG3/Quil A resulted in significantly more survival days and fewer brain cysts after challenge with T. gondii compared to an infected control group. Mice immunized with rSAG3 alone or in combination with Quil A produced significantly more specific IgG2a antibody, whereas specific IgG1 antibody titers did not increase. The percentage of CD8+ T cells, IFN-γ mRNA expression, and nitric oxide production significantly increased in rSAG3- and rSAG3/Quil A-immunized mice. CONCLUSION: These results indicate that vaccination with Toxoplasma rSAG3 results in partial protective immunity against T. gondii infection through induction of a Th1-type immune response, and that protective immunity is accelerated by the modulating effects of Quil A.